A case for democratic pluralism instead of democratic minimalism - Sadr, Omar (Frontiers in Political Science, 2024)
This paper proposes a theory of democratic pluralism instead of democratic minimalism developed by Shadi Hamid in his book “The Problem of Democracy”. Democratic pluralism will leverage pluralism to create a possibility for reconciliation between liberalism, secularism, religion, and democracy. It presents a framework of democratic pluralism based on four key elements: (1) a conception of democracy that includes performance and political action in the public sphere beyond electoral participation; (2) recognition of diversity and intercultural dialog, alongside the agonistic dimension of pluralism; (3) moderation of individual autonomy and identity politics; and (4) pluralistic accommodation of religion. The paper critiques Hamid’s monolithic notions of liberalism, secularism, and democracy, suggesting that more nuanced approaches to these concepts are necessary. It contends that rather than abandoning liberalism and secularism, exploring compatible versions of liberalism and Islam within a pluralistic framework offers a more promising path for reforming religion and polity in the Muslim world.